2012
DOI: 10.1371/journal.pone.0033017
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Total and Activated Src Kinase in African American and Caucasian Breast Cancer

Abstract: BackgroundSrc, a non-receptor tyrosine kinase is elevated in cancer with expression and activity correlated with cell proliferation, adhesion, survival, motility, metastasis and angiogenesis. There is limited data on Src expression and subcellular localization in breast cancer and no information about expression in racial/ethnic groups.Methodology/Principal FindingsThe present study evaluated Src expression, activity, and subcellular localization in triple negative breast cancer (TNBC) and ERα positive breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…S10, which shows that c-Src phosphorylation is nearly absent when MDA-MB 468 cells are treated with 50 nmol/L dasatinib. As in most TNBC cell lines (43,44), c-Src is membrane associated in MDA-MB 468 cells. We observed a profound change in c-Src localization upon treatment with UM-164, but no change in localization upon treatment with dasatinib (Fig.…”
Section: Um-164 Alters the Cellular Localization Of C-srcmentioning
confidence: 82%
“…S10, which shows that c-Src phosphorylation is nearly absent when MDA-MB 468 cells are treated with 50 nmol/L dasatinib. As in most TNBC cell lines (43,44), c-Src is membrane associated in MDA-MB 468 cells. We observed a profound change in c-Src localization upon treatment with UM-164, but no change in localization upon treatment with dasatinib (Fig.…”
Section: Um-164 Alters the Cellular Localization Of C-srcmentioning
confidence: 82%
“…With these results, we have uncovered the mechanism of how focal adhesion molecules PIPKI␥i2, Src, and talin converge into a signaling complex to support oncogenic growth of tumor cells. This could be an oncogenic axis required for in vivo tumor growth and metastasis, including that of triple negative breast cancers, where PIPKI␥ and Src are predominantly overexpressed (23,49). Furthermore, the elucidation of oncogenic signaling molecules downstream of PIPKI␥i2 and Src and their functional relevance in vivo are future directions for study.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant Src activation plays prominent roles in cancer formation and progression (Aleshin and Finn, 2010; Finn, 2008; Mayer and Krop, 2010). The Src pathway is one of the most commonly upregulated pathways in TNBC (Anbalagan et al, 2012; Tryfonopoulos et al, 2011). While Src inhibitors hold promise in treating metastatic TNBC (Pal and Mortimer, 2009; Tryfonopoulos et al, 2011), initial clinical studies using Src inhibitor monotherapy in unselected patients with advanced BC showed only minor response (Finn et al, 2011; Gucalp et al, 2011; Herold et al, 2011; Mayer and Krop, 2010).…”
Section: Introductionmentioning
confidence: 99%